Flexural-torsional buckling behaviour of fixed-ended hot-rolled austenitic stainless steel equal-leg angle section columns - Liang, Yating (2020)
The present paper shows an experimental and numerical modelling investigation of the flexural-torsional buckling behaviour and load-carrying capacities of fixed-ended hot-rolled austenitic stainless steel equal-leg angle section columns. The testing programme was conducted on four austenitic stainless steel angle sections and involved material testing, initial global and torsional imperfection measurements and sixteen fixed-ended column tests. This was followed by a numerical simulation study, where the numerical models were firstly developed to validate against the experimental data and then utilised to perform numerical parametric studies to generate additional results over a broader range of member lengths and cross-section geometric dimensions. The derived test and finite element results were carefully analysed and then utilised to evaluate the accuracy of the established design rules in Europe, America and Australia/New Zealand. Comparisons of the failure loads derived from the experimental and numerical studies with the corresponding codified flexural-torsional buckling strength predictions revealed an unduly high level of conservatism and scatter. Extension of the direct strength method to carbon steel equal-leg angle section columns has been recently made, and the applicability of the approach to fixed-ended hot-rolled austenitic stainless equal-leg steel angle section columns was also assessed. The new approach was generally shown to yield more precise flexural-torsional buckling resistance predictions than the existing design standards, but a large portion of the predictions were unsafe, indicating that further improvements are required.